Pea and Lentil Flours Increase Postprandial Glycemic Response in Adults with Type 2 Diabetes and Metabolic Syndrome - Donna M. Winham; Mariel Camacho-Arriola; Abigail A. Glick; Clifford A. Hall; Mack C. Shelley (Foods)
Pea and lentil flours are added to baked foods, pastas, and snacks to improve nutritional quality and functionality compared to products made solely with refined wheat flour. However, the effect of whole pulses versus their serving size equivalent of flour on blood glucose has not been investigated in persons with altered glycemic response. Health claims for whole pulses are based on a ½ cup amount whereas commercial pulse flour servings are typically a smaller size. The glycemic responses of four treatment meals containing 50 g available carbohydrate as ½ cup whole pulse or the dry weight equivalent of pulse flour were compared with a control beverage (Glucola®). Eleven adults with type 2 diabetes mellitus (T2DM) and eight adults with metabolic syndrome (MetS) completed the study. Venous blood samples were collected at fasting and at 30 min intervals postprandial for three hours. Changes in net difference in plasma glucose over time from baseline and incremental area under the curve (iAUC) segments were analyzed. All four pulse meals attenuated the iAUC compared to the control from 0 to 120 min for T2DM participants and 0–180 min for MetS participants. Whole pulses produced a lower glycemic response than pulse flours in the early postprandial period for persons with T2DM and during the overall test period for those with MetS.